Rethinking Modern Fatwa Typology: An Ethnographic Study on al-Azhar Fatwa Council - Al-Marakeby, Muhammad (Universitas Islam Internasional Indonesia, 2022)
This study addresses how al-Azhar's Lajnat al-Fatwa is situated in the modern context, and to what extent the taxonomy of official/non-official, traditional/modern, reformists/conservative may not help us in understanding the nature of the Lajnah. I argue that this kind of categorization can obscure rather than explain the Lajnah position. On the one hand, its fatwas are recognized by state institutions and courts as official; it toes the line on government policies discouraging political questions or debate; and it is influenced by the rational approach of modernity with regard to questions on jinn and sorcery. On the other hand, it challenges the nation-state's public policies on issues like bank interests, female circumcision, and mortgages; it lacks systematization that characterizes the modern institutions; and at least some of its members refuse to issue fatwas contradicting the established opinions of the four madhhabs. Many of those fatwas stand at odds with the views of Dār al-Iftāʾ, ‘The’ official fatwa institution in Egypt, which is more inclined to serve the national interests and programs of the government. The findings of this study encourage us to rethink our dichotomous classification of ulama and to avoid simplistic assumptions about fatwa councils in modern times. It shows how reality is more complicated, nuanced, and entangled than our sharply-defined categories.